3(x+4)-2(2+2x)=3(x-6x+10+12)

Simple and best practice solution for 3(x+4)-2(2+2x)=3(x-6x+10+12) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 3(x+4)-2(2+2x)=3(x-6x+10+12) equation:



3(x+4)-2(2+2x)=3(x-6x+10+12)
We move all terms to the left:
3(x+4)-2(2+2x)-(3(x-6x+10+12))=0
We add all the numbers together, and all the variables
3(x+4)-2(2x+2)-(3(-5x+22))=0
We multiply parentheses
3x-4x-(3(-5x+22))+12-4=0
We calculate terms in parentheses: -(3(-5x+22)), so:
3(-5x+22)
We multiply parentheses
-15x+66
Back to the equation:
-(-15x+66)
We add all the numbers together, and all the variables
-1x-(-15x+66)+8=0
We get rid of parentheses
-1x+15x-66+8=0
We add all the numbers together, and all the variables
14x-58=0
We move all terms containing x to the left, all other terms to the right
14x=58
x=58/14
x=4+1/7

See similar equations:

| x÷16.7=-0.7 | | x+4.5=-3.9 | | 3x-15=8x+2-9 | | 19n=13-7+n | | 798=3*n+47 | | 22-4x=12+6x | | x²-2,4x+1,44=0 | | -y/7=-51 | | 6x+12=8x-10-9x | | 4x-6=5x+6-x | | 6.3j–20=16 | | -v/6=-38 | | 3x+68=2x+116 | | 3y+2y-76=3y+11 | | 100=-2x^2+32x | | 4z2=144 | | 3x+7−x=21 | | 3x+7-x=2 | | -9x+81=3(x+63) | | 4c+3=-29 | | 16x+470=21x | | 7+y/3=-5 | | 37x=470 | | -5x-1=x-7 | | 21x+16=470 | | 2(4w-3)=42 | | 3(x+1)=7(x-2)=-3 | | x/4=4+-7 | | 12x+96=-3(x-47) | | -4(x-4)=2x-2 | | 8x+149=9x | | r2=0.75 |

Equations solver categories